CHALLENGES OF INCLUSIVE EDUCATION IN GEORGIA - Samarguliani, Nino (European Scientific Journal, ESJ, 2016)
The objective of this paper is to present the challenges that inclusive education system faces nowadays in Georgia. The paper reviews several issues connected with programs developed for supporting and further development of inclusive education in Georgia. The paper is aimed to describe the main problems and challenges and suggest their possible solutions.